2008
DOI: 10.1186/1471-2164-9-606
|View full text |Cite
|
Sign up to set email alerts
|

Differential RelA- and RelB-dependent gene transcription in LTβR-stimulated mouse embryonic fibroblasts

Abstract: BackgroundLymphotoxin signaling via the lymphotoxin-β receptor (LTβR) has been implicated in biological processes ranging from development of secondary lymphoid organs, maintenance of spleen architecture, host defense against pathogens, autoimmunity, and lipid homeostasis. The major transcription factor that is activated by LTβR crosslinking is NF-κB. Two signaling pathways have been described, the classical inhibitor of NF-κB α (IκBα)-regulated and the alternative p100-regulated pathway that result in the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
5
20
1
Order By: Relevance
“…IKKα regulates noncanonical NF-κB signaling by a group of TNF-like receptors, including lymphotoxin β receptor (LTβR) (19). LTβR activates NF-κB by proteasomal processing of the NF-κB precursor protein p100 into the mature p52 subunit, thereby stimulating expression of target genes including Ccl2 (20). As expected, in LTβR-exposed wild-type cells, we observed an accumulation of p52 protein and induced Ccl2 expression.…”
Section: Hocl Reversibly Inhibits Tnf-α-stimulated Nf-κb-dependent Gesupporting
confidence: 60%
See 1 more Smart Citation
“…IKKα regulates noncanonical NF-κB signaling by a group of TNF-like receptors, including lymphotoxin β receptor (LTβR) (19). LTβR activates NF-κB by proteasomal processing of the NF-κB precursor protein p100 into the mature p52 subunit, thereby stimulating expression of target genes including Ccl2 (20). As expected, in LTβR-exposed wild-type cells, we observed an accumulation of p52 protein and induced Ccl2 expression.…”
Section: Hocl Reversibly Inhibits Tnf-α-stimulated Nf-κb-dependent Gesupporting
confidence: 60%
“…The method used was a repeated-measures ANOVA for ordinal data. We considered two factors: treatment (control vs. HOCI) and time (14,20, and 30 days) and an interaction term (treatment × time). The treatment factor allowed us to study differences between the control and HOCI groups, the time factor allowed us to study differences among the three time points, and the interaction term allowed us to determine whether differences between the control and HOCI groups were consistent over time.…”
Section: Figurementioning
confidence: 99%
“…It has been shown that NF-kB represses tumor necrosis factor-a-induced autophagy in Ewing sarcoma cells through activation of mTOR (Djavaheri-Mergny et al, 2006). The reason for these discrepancies remains unclear, but it is possible that the dimeric composition of NF-kB, as in other physiological contexts, may determine the functional outcome of NF-kB activation (Bren et al, 2001;Lovas et al, 2008).…”
Section: V12mentioning
confidence: 94%
“…Selective recruitment of RelB to the promoter region of these genes and in vitro binding assays between NFκB dimeric complexes and DNA probes suggested that RelB:p52 recognizes specific κB-binding sites that are different from those bound by RelA:p50 [89]. However, genome-wide gene expression analysis derived from LTβR-stimulated MEF revealed that the majority of the induced genes require both RelA-and RelB-containing dimers [90]. RelB:p52 and RelA:p50 complexes derived from eukaryotic cells showed similar ability to bind to consensus binding sites [91].…”
Section: The Non-canonical Pathwaymentioning
confidence: 99%